Development of a PjBL Model Learning Program Plan based on a STEM Approach to Improve Students' Science Process Skills - Muhammad Syukri; Dewi Agusti Yanti; Elmi Mahzum; Abdul Hamid (Postgraduate, University of Mataram, 2021)
The purpose of the research is to developing Learning Program Plan (LPP) with a PjBL model based on the STEM approach to improve the students’ science process skills in physics learning. This research refers to the development of ADDIE, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation and 5) Evaluation. The worthiness of the Learning Program Plan is measure by the result of the Learning Program Plan validation and the responding of the subject is 7 teachers. The result of all the Learning Program Plan showing average value is 4, that is the valid category. The research design used in the study is Research and Developing (R&D). The research subject is 3 physics teachers at SMA Negeri 5 Banda Aceh, 1 physics teacher at SMA Negeri 1 Lawe Alas, 1 physics teacher at MA Negeri 1 Aceh Tenggara, and 2 physics teachers at SMA 3 Kutacane. Data of the research are questionnaires that are given to the teacher. Data management is carried out by Statistik analysis Likert scale. Questionnaire of the result showed until 89%. From both measures are found the development of Learning Program Plan model PjBL that teacher assessment result to Learning Program Plan with an average score 4.45 with the overall percentage based STEM approach to improving science process student skills in physics learning.